2000
DOI: 10.1152/ajpheart.2000.278.4.h1142
|View full text |Cite
|
Sign up to set email alerts
|

Determination of microvascular flow pattern formation in vivo

Abstract: Blood flow in microvessels differs significantly from that of red blood cells (RBC) flowing through long, straight glass tubes in vitro. The in vivo situation is characterized by the presence of plasma favoring aggregation, by the irregular geometry of vessel segments, and by frequent branching points. Here, a method is presented to characterize flow patterns in microvascular blood flow during intravital microscopy based on Fourier analysis of recorded light intensity patterns. The interpretation of the result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 26 publications
(24 reference statements)
1
10
0
Order By: Relevance
“…Similar findings have been previously reported by others [7,8,28,29]. On the basis of the formula used in our study, the hemodilution induces a reduction in WSS that in turn causes, as demonstrated by others, a modification in erythrocyte aggregation and aggregate size [30,31]. It is known that physiologically, in small vessels, erythrocytes tend to aggregate to form rouleaux reducing peripheral resistances.…”
Section: Discussionsupporting
confidence: 91%
“…Similar findings have been previously reported by others [7,8,28,29]. On the basis of the formula used in our study, the hemodilution induces a reduction in WSS that in turn causes, as demonstrated by others, a modification in erythrocyte aggregation and aggregate size [30,31]. It is known that physiologically, in small vessels, erythrocytes tend to aggregate to form rouleaux reducing peripheral resistances.…”
Section: Discussionsupporting
confidence: 91%
“…Some authors have advocated a more physiologic method in which the UW solution is flushed under pressure (100 mm Hg), similar to the mean arterial blood pressure with the advantage of perfusing the small intrahepatic vessels. Measurement of the microvascular blood flow patterns in physiologic conditions using intravital microscopy shows that in arterioles and venules with a diameter of 24.7 Ϯ 9.1 m, the recorded shear rate has a mean value of 201Ϯ163 sec Ϫ1 (21). The minimal value of the shear rate that prevented UWinduced aggregation in the authors' experiments was 175Ϯ29 sec Ϫ1 .…”
Section: Imaging Techniquesmentioning
confidence: 68%
“…RBC aggregability and deformability were investigated in vitro with a laser-assisted optical rotation cell analyzer (LORCA R&R Mechatronics, Hoorn, The Netherlands) (20,21). This instrument, based on the ektacytometric principle, is equipped with a video camera for detection of the laser diffraction pattern, a thermostation unit, and an ellipse-fit computer program calculating the Elongation Index and Aggregation Index (AI).…”
Section: Methodsmentioning
confidence: 99%
“…It is possible that these aggregates represent short-lived red cell clusters brought in close contact solely by hemodynamic forces as suggested by Osterloh et al (29). They reported a mean particle size considerably greater than that of red cells at high shear rates in pre-and postcapillary vessels (ϳ25 m) using a spatial Fourier analysis of light intensity patterns.…”
Section: Discussionmentioning
confidence: 86%
“…Not surprisingly, these aggregates formed further downstream, between 40 and 55 m from the entrance to the postcapillary venule. Osterloh and coworkers (29) found that the pattern size of particles in preand postcapillary vessels increased at pseudoshear rates both higher and lower than ϳ150 s after infusion of dextran 250 (800 mg/kg body wt). The presence of aggregation at high pseudoshear rates in their study and ours may be explained not only by the hemodynamic forces mentioned above but also by the macromolecules of dextran once the hemodynamic forces bring red blood cells into close contact.…”
Section: Discussionmentioning
confidence: 99%